Artificial nutrition dependence after cetuximab versus cisplatin combined with radiotherapy for advanced head and neck cancer: A propensity score–matched analysis. Issue 2 (16th September 2016) - Ishimaru, Miho; Ono, Sachiko; Suzuki, Sayaka; Matsui, Hiroki; Fushimi, Kiyohide; Yasunaga, Hideo
ABSTRACT: Background: The purpose of this study was to compare the effect of cetuximab‐based radiotherapy (RT) with cisplatin‐based concomitant chemoradiotherapy (CCRT) on artificial nutrition dependence in locoregional advanced head and neck cancer. Methods: We identified patients treated with cetuximab‐based RT or CCRT between 2012 and 2014 in a Japanese national database, and used propensity score‐matched analyses to evaluate artificial nutrition dependence for 30 days after starting chemotherapy and at hospital discharge. Results: Of 3935 eligible patients, propensity score matching generated 250 pairs. Thirty‐day artificial nutrition dependence was significantly lower in the cetuximab‐based RT group than in the CCRT group (25.6% vs 35.2%; odds ratio [OR] = 0.67; 95% confidence interval [CI] = 0.46–0.97; p = .036). No significant difference in artificial nutrition dependence at hospital discharge was shown (6.2% vs 7.2%; OR = 1.07; 95% CI = 0.52–2.17; p = .861). Difference in duration of hospitalization was insignificant. Conclusion: Cetuximab‐based RT may reduce short‐term artificial nutrition dependence compared to CCRT. © 2016 Wiley Periodicals, Inc. Head Neck 39: 320–325, 2017